The study of maternal and perinatal outcome in multiple pregnancies in tertiary care centre - Patil, Niraj; Deshmukh, Sonali; Shanbhag, Shirish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Multiple pregnancies, involving twins, triplets, or higher-order multiples, present unique challenges and risks to both maternal and perinatal health. These pregnancies are associated with increased complications such as preterm birth, preeclampsia, and fetal growth restrictions, making their management a significant concern in obstetric care. Methods: This hospital-based observational study, conducted from December 2017 to January 2019 in the department of obstetrics and gynaecology at a tertiary care center in Mumbai, examines maternal and perinatal outcomes in multiple pregnancies. The study population comprised pregnant women diagnosed with multiple pregnancies attending the hospital. Results: The study aimed to identify the prevalence and risk factors associated with adverse outcomes in multiple pregnancies to inform better clinical management and improve both maternal and neonatal health. Findings underscore the heightened risks associated with multiple gestations and emphasize the need for specialized antenatal care to mitigate these risks effectively. Conclusions: Key maternal outcomes assessed included rates of preeclampsia, gestational diabetes, preterm labor, and caesarean deliveries. Perinatal outcomes focused on preterm birth rates, low birth weight, neonatal intensive care unit (NICU) admissions, and perinatal mortality.